PENGARUH STRATEGI PEMBELAJARAN DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR AKIDAH AKHLAK SISWA MIN SEI MATI MEDAN - Rini Sartika (Universitas Islam Negeri Sumatera Utara Medan, 2019)
This study aims to find out and to stress: (1) the effect of the application oflearning strategies on students' Akidah Akhlah learning outcomes, (2) theeffect of learning motivation on student Akidah Akhlah learningoutcomes, and (3) the interaction between learning strategies and learningmotivation towards Akidah Akhlak learning outcomes. The population ofthis study was all students in class V MIN Sei Mati Medan consisting of 3classes. Based on Cluster Random sampling techniques. The researchinstrument is a test used to obtain learning outcome data andquestionnaires to obtain data on student learning motivation. The analysistechnique is two-way Anova at significance  = 0.05 followed by theScheffe test. The results showed: (1) the average learning outcomes ofstudents taught with collaborative learning strategies X = 28.15 higherthan the average learning outcomes of students taught with competitivelearning strategies X = 26.92, with Fcount = 29.57 > Ftable = 3.968, (2) theaverage learning outcomes of students with high learning motivation X =29.93 higher than the learning outcomes of students with low learningmotivation X = 25.94 with Fcount = 4.43 > Ftable = 3.968, and (3) there is aninteraction between learning strategies and learning motivation towardsAkidah Akhlak learning outcomes with Fcount = 7.18 > Ftable = 3.968.